(untitled) (Research, Society and Development, 2022)
Introduction: Cervical cancer (CCU) is a silent neoplasm, with HPV infection as the main risk factor. The early diagnosis of this cancer is promoted mainly by Primary Care, based on the Comprehensive Assistance Policy for Women’s Health (PAISM). Thus, October Rosa stands out as a campaign for the awareness and prevention of CCU by carrying out the cytopathological examination. Objective: To understand the importance of October Rose for the early diagnosis of cervical cancer in João Pessoa. Methodology: A survey was carried out to capture data in the Cancer Information System (SISCAN) and in the Health Information System for Primary Care (SIS-AB). Results: There was an average of 30,000 cytopathological tests performed between 2017-2019, with a drop in 2020 due to the COVID-19 pandemic. Virtually every year, Pink October has shown a positive impact, with an increase in the number of tests performed in that month and in the adjacent months. However, João Pessoa did not reach the target of the Cytopathological Coverage Indicator, due to sociocultural barriers. Conclusions: Pink October proved to be of immense importance for the early diagnosis and prevention of CC, contributing to greater longitudinality in women’s health care.